Imposition of Import Duty and Taxes in the Context of Importation of Medical Devices in terms of Basic Health Rights as Human Rights - Wahyu Andrianto; Fadhlan Zamzami Sitio; Atika Rizka Fajrina (Universitas Katolik Soegijapranata Semarang, 2021)
ABSTRACT: The right to health is one of the human rights listed in the Universal Declaration of Human Rights as a basic right of every individual and is non-derogable. Post- amendment, Article 34 paragraph (3) of the 1945 Constitution mandates;